The Prospect of Human in the Exegetical Work: a Study of Buya Hamka’s Tafsir al-Azhar - Ade Jamarudin; Asmal May; Ofa Ch. Pudin (Universitas Islam Negeri Mataram, 2019)
This paper elucidates Buya Hamka’s views on the prospect of humans on the earth while facing persistent challenges in their lives. This study is based on library research that focuses on Hamka’s work Tasfir al-Azhar. Tasfir al-Azhar represents a modern Quranic exegetical work written by a modern Indonesian Muslim scholar. This paper argues that in Hamka’s view, humans’ acts are created by their own since God has bestowed them as a perfect creature. With their sense, humans can weigh and distinguish between good and evil and between right and wrong. To Hamka, people are free to determine their own life. The perfect human is those who have a strong belief and mind to determine the direction of life. Furthermore, the future of humans depends on their will to move forward and know the consequences of their actions. In the Islamic context, as Hamka maintains, perfect human is reflected in the Muslim community who can maintain brotherhood, uphold equality and keep independence.